PENGARUH NILAI PELANGGAN SUPERIOR DAN PERSEPSI HARGA TERHADAP KEUNGGULAN BERSAING BERKELANJUTAN DAN DAMPAKNYA TERHADAP LOYALITAS PELANGGAN (Studi pada Pengguna Smartphone Merek Smartfren di Kota Semarang) - Bayu Iriyanto Hutama, 12.42.02.0043; Tjahjaningsih, Endang (Jurnal Mahasiswa Pasca Sarjana, 2014)
Smartphone market is saturated and more competitive level of competition, making it difficult for companies to apply superior strategy than its competitors. Smartphone Smartfren brand was first marketed in June 2013, and was already able to occupy the second rank and the only local vendor in the top five for smartphone sales in Indonesia in the Year 2013 to Quarter IV. Smartfren use strategies in order to create sustainable competitive advantage of customer loyalty. This strategy involves creating a product that can deliver superior customer value and low price. Research on the influence of superior customer value and price perception towards sustainable competitive advantage and its impact on customer loyalty is still relatively limited and inconsistent results. Therefore, this study aimed to analyze the influence of superior customer value and price perception towards sustainable competitive advantage and customer loyalty The research sample set of 100 people Smartfren brand smartphone customers in the city of Semarang. The sampling technique used purposive sampling. Data obtained by using a questionnaire, and then analyzed using path analysis. The results showed that superior customer value and price perceptions directly influence customer loyalty. Superior customer value and price perceptions indirect effect on customer loyalty through sustainable competitive advantage. Sustainable competitive advantage influence on customer loyalty. Keywords: Â Â superior customer value, price perception, sustainable competitive advantage and customer loyalty